The effects of mastery learning model on the success of the students who attended usage of basic information technologies course - Kazu, IY; Kazu, H; Ozdemir, O (Int Forum Educational Technology & Soc, Natl Taiwan Normal Univ, 2005)
In order to realize one of the most important necessities of the life, which is learning, the human being spends most of their life for education-training activities. In the conventional applications, every individual, being a part of a group is dependant on a single program and an educational management which was chosen for the group by the teacher. However, each student has individual learning abilities, different from other members of the group. At the end of the teaching activities with one group, nearly all of the individuals of that group are expected to be successful. This study was performed at the Technical Education Faculty of F1rat University in Elazig during 2002-2003 autumn term in order to determine the effects of this mastery learning model on the success of the students who attended the Usage of Basic Information Technologies course. The findings gained in this research show that being a significant difference in experiment group favour on the points of final test and achievement points. (The findings of the study show a significant difference in favor of the experimental group, versus the control group, in both the final test scores and achievement points.) In experimental group, mastery learning model was used. Therefore, it was seen that mastery learning model increased the student achievement effectively.
Keywords: mastery learning; individual differences; technology education; information technologies